2020
DOI: 10.4314/gmj.v54i4s.5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of COVID-19 in Ghana: symptomatology, illness severity and comorbid non-communicable diseases

Abstract: Objective: This analysis described the clinical features of COVID-19 in the early phase of the pandemic in Ghana.Methods: Data were extracted from two national COVID-19 treatment centers in Ghana for over 11 weeks(from March to May 2020). Descriptive and inferential statistics were performed. Modified Ordered Logistic and Negative Binomial Regression analysis were applied to establish factors associated with illness severity and Non-communicable Disease (NCDs) counts respectively. All analysis was conducted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…25 Further research is needed to clarify the role of symptom burden, earlier exposure to coronaviruses or differences in genetic vulnerability to symptoms in explaining the seemingly high proportion of asymptomatic cases in Ghanaians. [26][27][28][29] Alternatively, recall of symptoms, particularly mild symptoms, could have been lower in this group, which might be explained by lower levels of health literacy, knowledge of COVID-19 symptomatology and possibly education when compared with other groups. Furthermore, selfassessment of infection might have been under-reported during the face-to-face interview due to fear of stigmatisation or social desirability bias.…”
Section: Open Accessmentioning
confidence: 86%
“…25 Further research is needed to clarify the role of symptom burden, earlier exposure to coronaviruses or differences in genetic vulnerability to symptoms in explaining the seemingly high proportion of asymptomatic cases in Ghanaians. [26][27][28][29] Alternatively, recall of symptoms, particularly mild symptoms, could have been lower in this group, which might be explained by lower levels of health literacy, knowledge of COVID-19 symptomatology and possibly education when compared with other groups. Furthermore, selfassessment of infection might have been under-reported during the face-to-face interview due to fear of stigmatisation or social desirability bias.…”
Section: Open Accessmentioning
confidence: 86%
“…Our findings also showed that common cold, asthma, and hypertension were common health conditions reported. It is known that whilst common cold/flu and fever may be experienced in the early stages of COVID-19, among other respiratory symptoms like cough and dyspnea ( Ahmad et al, 2021 ), asthma, diabetes, and hypertension may complicate the outcome of coronavirus infections ( Yawson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study conducted on COVID-19 patients in Ghana showed that people with the most common underlying illnesses, such as hypertension, diabetes, asthma, heart disease, and chronic kidney disease were diagnosed with COVID-19 ( 13 ). This places older adults, particularly those suffering from diabetes and hypertension, at a higher risk for severe illness from COVID-19 ( 14 ), resulting in an increase in stress, depression, and isolation during the peak of COVID-19 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%